Turnkey or Tailored? Relational Pluralism, Institutional Complexity, and the Organizational Adoption of More or Less Customized Practices - Raffaelli, Ryan; Glynn, Mary Ann (Academy of Management Journal, 2014)
We examine how the organizational adoption of new practices is influenced by relational pluralism, i.e., an organization's multiple ties to actors inside and outside its industry. We theorize that institutional mechanisms of practice diffusion underlying relational networks and filtered by organizational characteristics influence the adoption of practices that are more customized (tailored) or less customized (turnkey). We hypothesize, first, that organizations participating in extra-industry professional networks will, through normative conformity, be more likely to adopt turnkey practices; second, that the normative pressure of professional networks will interact with the mimeticism of industry peers such that organizations will be more likely to adopt tailored practices; and third, that organizational filters will affect adoption of all practices. Using unique survey data from 161 Fortune 500 organizations, supplemented by archival and qualitative data, we focus on two corporate social responsibility practice variants. We find significant support for our first two hypotheses and mixed support for our third: Organizational infrastructure and identity significantly affect practice adoption, albeit in different ways, but only marginal support for leadership and elite organizational status. Our results point to how a complex web of relational ties affects the organizational adoption of practice variants that differ in their degree of customization.